Presentation, Diagnosis and Treatment Delays in Breast Cancer Care and Their Associations in Sri Lanka, a Low-resourced Country. Issue 9 (September 2022) - Hewage, S.A.; Samaraweera, S.; Joseph, N.; Kularatna, S.; Gunawardena, N.
Abstract: Aims: Delays in breast cancer care, one important attributable factor for breast cancer being diagnosed at advanced stages, are not systematically studied in many countries. This study assessed the magnitude and factors associated with delays in breast cancer care in Sri Lanka, from symptom detection to treatment initiation. Materials and methods: We interviewed 800 consecutively sampled female breast cancer patients, diagnosed within the last 12 months, using context-specific questionnaires and medical records. We defined the cut-off times for delays using international guidelines and features of the national health system and care-seeking patterns in the country. Delays were estimated as proportions with 95% confidence intervals and presented for: (i) presentation delay; (ii) diagnosis delay and (iii) treatment delay. We looked at how sociodemographic and healthcare availability and accessibility at the individual level were associated with delays using multivariate logistic regression, with a P value of 0.05 to define statistical significance. Results: Nearly two-thirds of patients reported a presentation delay (63.3%, 95% confidence interval 59.9–66.6%). A diagnosis delay (36.7%, 95% confidence interval 33.4–40.0%) was also seen among one-third, whereas treatment delays (13.2%, 95% confidence interval 10.8–15.5%) were less common. Low family monthly income (odds ratio 6.3; 95% confidence interval 4.2–9.3) and poor knowledge on breast cancer (odds ratio 2.7; 95% confidence interval 1.8–3.8) were associated with presentation delay. Poor health literacy (odds ratio 1.7; 95% confidence interval 1.1–2.7) and the need to make more than two visits to the first contact health provider prior to diagnosis (odds ratio 7.2; 95% confidence interval 4.6–11.1) were associated with diagnosis delays, whereas directly contacting an appropriate specialised health provider once the lump was detected reduced diagnosis delay (odds ratio 0.3; 95% confidence interval 0.2–0.4). Having undergone a core biopsy (odds ratio 0.5; 95% confidence interval 0.3–0.8) and having a mammogram (odds ratio 0.6; 95% confidence interval 4.7–32.7) reduced the likelihood of treatment delays. Conclusions: Our study findings show that delays in breast cancer care in Sri Lanka are much lower than those in other lower-middle income countries. However, there is significant room for improvement, especially in relation to the excellence in quality of care, such as improving access to mammography services. Periodical estimation of breast cancer delays enabling temporal comparisons will probably provide useful information to policy makers in improving care delivery for breast cancer patients and, hence, is recommended. Such future assessments designed for comparisons between different treatment modalities would provide more information to assist policy decisions in care improvement. Highlights: Most breast cancer patients in Sri Lanka detect breast lesions by themselves. Delays in breast cancer care in Sri Lanka are much less than in other lower-middle income countries. However, there is significant room for improvement in the quality of care. Periodical delay estimations are encouraged to direct improvements in care.